Low‐complexity GNSS anti‐spoofing technique based on Doppler frequency difference monitoring. Issue 9 (8th August 2018) - Tu, Jiaxun; Zhan, Xingqun; Zhang, Xin; Zhang, Zhenjun; Jing, Shuai
Abstract : Single‐antenna global navigation satellite system (GNSS) spoofing, where all spoofing signals are broadcast by the same antenna, is a great threat to mass market location‐based services. This study proposes an anti‐spoofing technique based on Doppler frequency difference (DFD) monitoring against single‐antenna spoofing, which requires only a standalone receiver with a single antenna. When the receiver moves randomly, the DFD between two authentic satellite signals is non‐linear in time domain, whereas between two single‐antenna spoofing signals is linear. This study deduces the DFD model and converts the problem of spoofing detection into a sequence linearity detection problem. The hypothesis based on DFD is given, and the statistic is constructed by the method of sequence block processing. This technique has low complexity because it only requires the knowledge of the Doppler frequency without additional information. The detection performance is verified by simulations and real data experiments. The simulation results show that the detection probability can exceed 99.99% easily at 0.001% false alarm probability when the receiver's motion state changes sufficiently. The real data experiments show that the proposed technique can effectively detect GNSS spoofing and distinguish spoofing signals from authentic signals.